Bank capital, the state contingency of banks' assets and its role for the transmission of shocks - Michael Kühl (Deutsche Bundesbank, 2014)
The role of bank capital as a propagation channel of shocks is strongly pronounced in recent macroeconomic models. In this paper, we show how the evolution of bank capital depends on the share of non-state-contingent assets in banks' balance sheets and present the consequences for macroeconomic dynamics. State-contingent securities impact on banks' balance sheets through changes in their returns (and their prices), both of which depend on the current state of the economy. Nonstate-contingent assets are signed before shocks are realized and their repayment is guaranteed. For this reason they insulate banks' balance sheets from recent economic activity in the absence of defaults. Our results show that non-state-contingent assets in banks' balance sheets attenuate the amplification of shocks resulting from financial frictions in the banking sector.
Keywords: E44; E58; E61; 330; bank capital; state-contingent assets; non-state-contingent assets; monetary policy; financial frictions